Impact of Amino Acid Addition on Aroma Compounds in Papaya Wine Fermented with Williopsis mrakii - Lee, P.-R.; Yu, B.; Curran, P.; Liu, S.-Q. (South African Journal of Enology and Viticulture, 2011)
The impact of amino acid addition on aroma compound formation in papaya wine fermented with yeast Williopsis saturnus var. mrakii NCYC2251 was studied. Time-course papaya juice fermentations were carried out using W. saturnus var. mrakii NCYC2251, with and without the addition of selected amino acids (L-leucine, L-isoleucine, L-valine and L-phenylalanine). Yeast growth and changes in sugars, °Brix, organic acids and pH were similar, regardless of amino acid addition. L-Leucine addition increased the production of isoamyl alcohol and some esters such as isoamyl acetate, isoamyl butyrate and isoamyl propionate, while L-isoleucine addition increased the production of active amyl alcohol and active amyl acetate. L-valine addition slightly increased the production of isobutyl alcohol and isobutyl acetate. L-phenylalanine addition increased the formation of 2-phenylethanol, 2-phenylethyl acetate and 2-phenylethyl butyrate, while decreasing the production of most other esters. This study suggests that papaya juice fermentation with W. saturnus var. mrakii NCYC2251 in conjunction with the addition of selected amino acid(s) can be an effective way to modulate the aroma of papaya wine.